Glycoprotein VI is associated with GPIb-IX-V on the membrane of resting and activated platelets - Arthur, Jane F.; Gardiner, Elizabeth E.; Matzaris, Maria; Taylor, Simon G.; Wijeyewickrema, Lakshmi; Ozaki, Yukio; Kahn, Mark L.; Andrews, Robert K.; Berndt, Michael C. (Thrombosis and Haemostasis, 2005)
The platelet collagen receptor, glycoprotein (GP)VI, initiates platelet aggregation at low shear stress while GPIb-IX-V, which binds von Willebrand factor, elicits platelet aggregation under high shear conditions. To investigate the possibility that GPIb-IX-V and GPVI are associated on the platelet surface, we first ascertained that aggregation induced by a GPVI-specific agonist, collagen-related peptide, like collagen, is markedly cross-blocked by a GPIbα-specific monoclonal antibody, SZ2. Immunoprecipitation of GPIb-IX with anti-GPIbα from the 1% (v/v) Triton-soluble fraction of unstimulated platelets and immunoblot-ting with anti-GPVI demonstrated association between GPIb-IX and GPVI. This association was maintained when platelets were activated by thrombin. Pre-treatment of platelets with methyl-β-cyclodextrin to disrupt lipid rafts did not affect association in resting platelets under these conditions of detergent lysis. The association is also independent of cytoskeletal attachment, since it was unaffected by treatment with N-ethylmaleimide or DNaseI, which dissociate GPIb-IX from filamin and the actin-containing cytoskeleton, respectively. Finally, the association involves an interaction between the ectodomains of GPIbα and GPVI, since soluble fragments of GPIbα (glycocalicin) and GPVI are co-precipitated from the platelet supernatant under conditions where GPVI is shed. A contribution of GPIb-IX-V to GPVI-induced platelet responses, and vice versa, therefore warrants further investigation.
Keywords: Platelet physiology; adhesion molecules; protein function/activity